O consumo e a representação da felicidade em 40 anos de propaganda brasileira - CARVALHO, Camila da Silva (2010)
This research is born from the comment of that, the consumption culture if presents as basic space of the societies contemporaries and affects questions of the daily life directly, through material and symbolic structures. Supporting itself in the studies of Slater, Lipovetsky, Featherstone, Baudrillard and Bourdieu it will be tried to delimit the historical process of formation of what we call culture of the consumption placing in focus the forms as this culture articulates the questions relative to the forms of organization of the society having implications in the formation and negotiation of values, identities and felt central offices. This rank, will go to proceed itself to the inquiry from as the advertising, craftsman of this culture of consumption, has if busy, throughout the years in attributing to meanings and values to the goods and the experience of the consumption through the use of discursive strategies and symbolic elements coing-opt the speech of the happiness using it as substance cousin, reprocessing and constantly returning to this ideal of happiness under the form of campaigns and sensorial experiences of consumption. Another central point of this study, the delimitation of what emerges from there it is the happiness, for in such a way, will serve base the historical and philosophical studies of McMahon (2006), Bosh (1998), Bruckener (2002), Conte-Sponville (2006) among others in the attempt to perceive the ideal of the happiness as a subjective and cultural concept that reflects and refracts the values basic of the individuals and if it differentiates as the historical and social moment. The main point will be then, to analyze as the concept of happiness in last the 40 years of the Brazilian advertising (1968- 2008) was worked, and to understand as this ideal was translated by the narratives advertising executives.